PENGARUH DUKUNGAN SOSIAL ORANG TUA DAN PENGALAMAN ORGANISASI TERHADAP KECERDASAN EMOSIONAL REMAJA DI ORGANISASI MAHASISWA UNIVERSITAS NEGERI JAKARTA - Bayu Tresna Aji; Hasanah, Uswatun; Nugraheni, Prastiti Laras (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2022)
Entering was revolution industry 4.0 Indonesia faced with the problem level unemployment open inside it including teenager graduate university that unemployed continue to increase. Some expertise is needed to succeed in the face the dynamics of world work that continues to change wrong only one is intelligence emotions that influenced factor external and internal. The research aims to know the influence of Parental Social Support and experience organization on the emotional intelligence of adolescents in organization college students at the State University of Jakarta with quantitative method research with formula problem associative. The population in the study is composed of college students who became members organization at 20 organization college students at the State University of Jakarta. Technique taking a sample with to use technique proportionate random sampling with use formula Slovin in the obtained total proportional model as much 272 college students. Research this done During October-December 2020. Result research shows the influence that positive and significant a manner simultaneous Among Parental Social Support and experience organization to intelligence emotional. It is proven with analysis regression multiple linear ones showing statistics positive Ŷ=24,333+0,252X1+0,491X2 and the result coefficient determination variable Parental Social Support and Experience Organization influence variable Emotional Adolescents with presentation amounting to 0.168 or 16.8% and the rest of to 83.2% influenced by other variables.